Application of Empty Oil Palm Bunches as CMC to Prevent Loss Circulation - Idham Khalid; Novia Rita; Muhammad Efras (Universitas Islam Riau (UIR) Press, 2021)
Drilling is an activity carried out to obtain the desired target. Furthermore, drilling mud a very significant material involved in the drilling process, and must, therefore, obtain a rational value from the rheology. A suitable technique to achieve this goal is the use of additives, for instance, Carboxymethyl Cellulose (CMC) to improve the viscosity and air binding. This study, therefore, uses CMC produced from organic oil palm bunches as an alternative for industrial CMC. CMC of Oil Palm Empty Bunches have been tested by Energy Dispersive X-ray Spectroscopy (EDS) to determine its composition. The Empty Oil Palm Oil which uses Tenera type was taken from Riau Province, Rokan Hulu Regency, Kunto Darussalam District. In this study, this experiment used CMC Empty Oil Palm and industrial CMC to find the value of viscosity, plastic thickness, melting point, gel strength, mud cake, and filtering volume of drilling mud and prevent the loss circulation with adding each CMC composition to mud samples with amount of 2 gr, 4 gr, 6 gr, 8 gr and 10 gr. According to the EDS analysis, the Carbon (C) and Oxygen (O) content of CMC from empty oil palm bunches were 58.85% and 41.15%, respectively. In addition, the industrial standard for plastic viscosity and yield point were not attained by using 8 gr and 10 gr of this CMC.